Use of modified Madou–Leblond model to predict crack initiation in low alloy steel specimens with different stress states. (January 2023) - Kumar, Suranjit; Samal, M.K.; Singh, P.K.; Chattopadhyay, J.
Abstract: This paper aims to predict the ductile fracture in low alloy steel specimens with pure tension, pure shear and combined shear–tension type loading using modified Madou–Leblond (MML) porous plasticity model, proposed by the present authors in a recent work. This model includes the effect of localised mode of plastic deformation in a narrow band through the definition of localised porosity level under shear dominated loading conditions. The damage parameter includes contributions due to void growth process under high stress triaxiality level as well as that due to shear localisation process under low stress triaxiality conditions. Experiments have been performed on the round tensile specimen, flat type shear specimen and combined shear–tension specimen. The numerical simulations results obtained using MML model has been compared with those of experiments. It has been shown that the MML model performs well in the prediction of the material softening behaviour and critical fracture location along with the fracture profile in all three types of specimens. Highlights: A modified Madou–Leblond (MML) model has been used to predict the fracture behaviour under different stress states. Damage variable captures the damage contribution due to defused and localised deformation. Experiments has been performed on low-alloy-steel material under different loading condition. The capability of MML model has been demonstrated with respect to experimental results. Model prediction for softening behaviour and crack initiation location has been compared with experiments.